Management in patient with rheumatoid arthritis and tuberculous arthritis: a case report - Huwae, Thomas E. C. J.; Santoso, Agung R. B.; Heifan, Ahmad; Siahaan, Lasa D. (International Journal of Research in Medical Sciences, 2021)
Rheumatoid arthritis (RA) is mainly treated with immunosuppressive drugs, which affects the immunological system. Therefore, the risk of tuberculosis was increased two to ten times in RA patients. Moreover, immunosuppressant is contraindicated in patients with tuberculosis arthritis. A 51-year-old male was presented with pain in his left elbow after he slipped on the floor. He was diagnosed with RA for 16 years and only took prednisone for six years. Six months before, he came to a rheumatologist and was given corticosteroid for six months for RA. The left elbow radiograph and joint aspiration revealed a tuberculosis infection. The patient treated with chloroquine and oral antituberculosis for one year and showed good clinical outcomes. Other diseases should be suspected in RA with uncommon symptoms. Chloroquine is the drug of choice in RA patients with tuberculosis who are contraindicated in immunosuppressant therapy because chloroquine has no immunosuppressant effect.